1998
DOI: 10.1046/j.1537-2995.1998.38898375514.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fetal red cells in fetomaternal hemorrhage using a fetal hemoglobin monoclonal antibody by flow cytometry

Abstract: The anti-HbF flow cytometric method for detection of fetal cells offers a simple, reliable, and more precise alternative to the Kleihauer-Betke manual technique for the assessment of fetomaternal hemorrhage. The method has additional potential applications for the study of HbF levels or frequency of adult red cells with low levels of HbF (F cells) in individuals with hemoglobinopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…However, this assay lacks specificity and exhibits a large inter-observer variation resulting in potential overtreatment risks related to plasma-derived products and unnecessary treatment cost (20)(21)(22). In accordance with previous studies, we reported an overestimation of FMH by the KBT (12,15,23). The KBT presents stained maternal F cells that may be counted as fetal RBCs, leading to these false positive results (20,23,24).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, this assay lacks specificity and exhibits a large inter-observer variation resulting in potential overtreatment risks related to plasma-derived products and unnecessary treatment cost (20)(21)(22). In accordance with previous studies, we reported an overestimation of FMH by the KBT (12,15,23). The KBT presents stained maternal F cells that may be counted as fetal RBCs, leading to these false positive results (20,23,24).…”
Section: Discussionsupporting
confidence: 87%
“…We found a coefficient of variation lower than 20% for values higher than 10 fetal RBCs per 10,000 maternal RBCs (0.1%) which is better than the KBT and in accordance with previous studies (4,13). Additionally, the kit design includes a positive marker of nucleated cells, thus facilitating exclusion of these interfering cells with autofluorescence levels similar in fluorescein isothiocyanate (FITC) fluorescence intensity as anti-HbF labeled fetal RBC (12,27). We adapted the gating strategy to enhance the fetal RBCs discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the use of anti-fetal haemoglobin antibodies for the detection of fetal cells by flow cytometry has been described (Davis et al, 1998 (Scott, 1996).…”
mentioning
confidence: 99%